Foliar application of Boron, Calcium, and Indole-3-butyric acid on onion plants to improve seed production - Gabri Martin, Carlos Guillermo; Soto Vargas, Verónica Carolina; Ibañez, Antonio; Galmarini, Claudio Romulo (Elsevier, 2025)
Onion is the third most important cultivated vegetable crop around the world. Two types of varieties are cultivated: Open pollinated cultivars (OP) and first generation hybrids (F1). Little is known about the effects of foliar applications on onion seed production. This study was conducted to evaluate the enhancement of onion seed yield and seed quality through foliar applications of Boron (B), Calcium (Ca), and an auxin, indole-3-butyric acid (IBA). Male-sterile lines (MSL), and OP planted in pots and open field conditions were used over four seasons. The experiments were carried out with different levels of nutrients and IBA applied to the plants. Our results showed that foliar applications of nutrients and plant growth regulators were effective methods to improve onion seed yield and the number of seed per fruit, while seed quality parameters remained stable. The seed yield was enhanced by B by up to 83 %, but with an increasingly wide variability in comparison to the control. Indole-3-butyric acid improved yields when it was applied alone and mixed with B and Ca (40–45 % for OP and MSL, respectively) compared to the control. Therefore, foliar application of IBA, B and Ca could be effective in improving onion seed yields.